Managing diversity: what does it mean? An analysis of different approaches and strategies - Elena Pietschmann (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
An increasingly complex aid landscape makes it urgent to find ways for partner countries to manage the diversity of aid actors and channels. However, it remains unclear what `managing diversity' actually means and how this vague idea should be put into practice. This paper explores potential approaches and strategies. It defines `managing diversity' as the management of different sources of aid by the partner country, aimed at improving the effectiveness of aid in a complex aid landscape. Different approaches to managing diversity are discussed and compared. Drawing on country experiences, the paper also analyses the role that contextual factors play in shaping incentives for the actors involved to implement different aid coordination strategies. Despite the multiplicity of possible strategies and approaches to managing diversity, some elements can be identified that will be crucial for every approach to aid coordination. To enhance their ability to effectively manage multiple actors and sources of development assistance, partner countries should develop clear aid policies and set up strong aid management institutions. Where needed, donors should support partner country leadership and capacity development in the area of effective aid management.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Entwicklungsfinanzierung und öffentliche Finanzen